2023
DOI: 10.1186/s12884-023-05552-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 2016 Chinese second-child policy and different maternal age on pregnancy outcomes in Hebei Province, China

Abstract: Objective To explore the effect of the 2016 Chinese second child policy and different maternal ages on adverse perinatal outcomes. Methods Clinical data were collected from 22 monitoring hospitals in Hebei Province from January 1, 2013, to December 31, 2021. A total of 413,892 parturient were divided into 3 groups based on delivery age: 20–34, 35–39, and 40–55 years old. The clinical data were analyzed to explore the relationship among the 2016 Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A similar decreased birth rate in the year of the goat was also reported in another study conducted in Hebei Province, China. 19 The data in this study showed a sharp increase in birth numbers in 2016, reaching the peak over the 10-year study period. The increase might be due to the introduction of the universal ‘two-child’ policy in 2015.…”
Section: Discussionmentioning
confidence: 53%
“…A similar decreased birth rate in the year of the goat was also reported in another study conducted in Hebei Province, China. 19 The data in this study showed a sharp increase in birth numbers in 2016, reaching the peak over the 10-year study period. The increase might be due to the introduction of the universal ‘two-child’ policy in 2015.…”
Section: Discussionmentioning
confidence: 53%
“…One plausible explanation for this decrease was the implementation of the universal two-child policy and comprehensive interventions to reduce unnecessary cesarean Sect. [ 15 ]. Another potential cause was the preference of nulliparous women for vaginal delivery to prevent the potential adverse consequence of cesarean section in the following pregnancy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AMA is on the rise worldwide, with rates reaching 20% in the United States and 33.4% in Korea [24,25]. In China, the reported proportion of women with AMA ranges from 8 to 15% of all births, especially that of first births among women of AMA, which are progressively increasing [6,26,27]. Age-related infertility often coexists with delayed childbearing, leading to increased demands for ART treatment among women of reproductive age [28].…”
Section: Discussionmentioning
confidence: 99%